PENGARUH MORALITAS DAN KESADARAN TERHADAP KEPATUHAN WAJIB PAJAK UMKM DENGAN MEMANFAATKAN FASILITAS PERPAJAKAN DI MASA PANDEMI COVID-19 (Studi Kasus Pada UMKM Yang Terdaftar di KPP Pratama Malang Utara) - Novita Dian Kusuma Putri; Nur Diana; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2022)
Taxes have an essential role in development in Indonesia. Taxpayers obedient to paying taxes are a manifestation of community participation in-state development. The success of tax collection depends on people's compliance in paying taxes. Tax compliance is crucial in supporting state revenues from the tax sector. However, during the Covid-19 Pandemic, many business actors experienced a decline in sales turnover, so the government implemented a policy of providing tax incentives to encourage taxpayer compliance in carrying out their obligations. This paper was conducted to determine the effect of taxpayers' morality and awareness on taxpayer compliance mediated by utilization tax facility incentives during the covid-19 pandemic. The research design used explanatory causality—methods of data collection with field surveys. The data source is primary. The unit of analysis was the individual. The sampling technique is simple random sampling. Owners and managers of MSMEs responded with a number of samples is 112. Time horizon using one-shot study. Data analysis using SEM Analysis.Keywords: MSMEs, PMK 82 tax facilities, morality, awareness, and MSME taxpayer compliance.